Polyphase‐coded incoherent scatter measurements at Millstone Hill. Issue 5 (13th September 2013) - Virtanen, Ilkka I.; Lind, Frank D.; Roininen, Lassi; Erickson, Philip J.; Rideout, William C.; Orispää, Mikko; Vierinen, Juha; Lehtinen, Markku S.
<x xml:space="preserve">Abstract</x> [1] We report first results of polyphase‐coded incoherent scatter measurements at Millstone Hill. To our knowledge, these are the first incoherent scatter measurements with polyphase alternating codes of Markkanen et al. (2008) and optimal quadriphase sequences of Damtie et al. (2008). The results demonstrate that an arbitrary waveform generator recently installed at the Millstone Hill incoherent scatter radar, part of the National Science Foundation Geospace Facility operated by the Massachusetts Institute of Technology Haystack Observatory, is capable of reproducing the polyphase waveforms with an accuracy sufficient for incoherent scatter measurements. Polyphase codes will allow incoherent scatter radar experiments to be better optimized, because they provide a larger variety of code and code cycle lengths than the traditional binary codes.